A History of Librarianship in Mexico 1912 – 1948: how it became recognized as a profession - Morales Becerra, Israel (Revista General de Información y Documentación, 2012)
An historical analysis of the process through which librarianship became a profession in Mexico between the years 1912 and 1948. Social and cultural factors which influenced and allowed for the changes in the social status of this occupation are identified.
Keywords: Librarianship in Mexico; history; background; institutionalization; Vasconcelos; School of Librarians.